The Investigate Factors on Screening of the Breast Cancer Based on PEN-3 Model in Iranian Northern Women - Seyed Abolhassan Naghibi; Mahmood Moosazadeh; Davood Shojaizadeh; Ali Montazeri; Jamshid Yazdani Cherati (Shahid Sadoughi University of Medical Sciences, 2015)
Introduction: As much as the women`s behavior for the premature diagnosis of the breast cancer is affected by the cultural and social factors, the purpose of this study is to investigate factors associated with screening accordance with the model PEN-3. Materials and Methods: The present study was cross-sectional. The samples studied were women above 20 years and the sample size was 1416 people. The method of sampling was a random cluster. The tools of data collection questionnaire with 70 questions which approved its content validity and reliability. Data were analyzed by using software of SPSS Ver. 20. Results: The average age of samples was 35.71±6.1. Only 14.3% of samples are regularly conducted to the self-examination. Also, 38.5% of women had a history of the clinical examination. The difference of observed in performance the breast self-examination and clinical breast examination were the statistical significant by variables of rural or urban (P= 0.005), the marital status (P = 0.013) and a background of having breast cancer (P <0.001). The results of the study based on PEN-3 model were showed that there were a statistical significant relationship between the structure of perceptual factors and reinforcing factors (P=0.002) and between the perceptual factors and enabling factors (P=0.006). Conclusion: According to the results of presented, the women`s performance in using the screening was low. Also, the components status of the PEN-3 Model (factors of perceptual, enabling, and reinforcing) for the breast cancer screening in women studied were not suitable.